EDS-related Feeding Difficulties: Preventing the Placement of a Surgical Feeding Tube. Issue 1 (16th February 2022) - Kilgore, Alexandra L.; Hawa, Juliette T.; Liu, Edwin; Belkind-Gerson, Jaime; Santucci, Kourtney Kuss
Abstract : Feeding difficulties due to functional gastrointestinal (GI) symptoms (i.e., nausea, pain, and bloating) are well described in patients with hypermobile-type Ehlers-Danlos Syndrome. These symptoms are particularly difficult to treat when there is comorbid dysautonomia, usually manifesting as postural orthostatic tachycardia syndrome. Here, we describe a successful trial of multidisciplinary rehabilitative interventions to avoid placement of a surgical feeding tube in such a patient. Main components of intervention were intensive pelvic floor physiotherapy and biofeedback, occupational therapy focused on coping with feeding-related symptoms, psychology support, and medications targeting histamine blockade and enhancing intestinal motility.